Colonic Transit Time Evaluation in Patients with Functional Constipation: - Taheri, Masoud; Rafiei, Rahmatollah; Torabi, Zahra; Toghiani, Ali; Taherzadeh, Sina (Galen Medical Journal, 2013)
Introduction: Functional constipation is one of the most common gastrointestinal symptoms which could affect patients’ quality of life. The colonic transit time test could be used for determining functional constipation subtypes. The aim of our study was to determine the abnormalities of the subtypes of functional constipation using CTT. Methods and Materials: This cross-sectional study was performed on 85 patients in 2011 in Shariaaty Hospital, Isfahan. All the patients received 60 radio-opaque markers, and they underwent radiological evaluation 5 days afterwards. Functional constipation was determined according to the distribution of the markers in the colon. Result: The samples consisted of 24 males and 61 females at a mean age of 42.7 ± 16.28 years. The colonic transit time results showed that 71 patients had normal transit time, 6 had a composite type, 5 had slow transit, and 3 had pelvic delay. There was no significant difference between sex and colon transit time types (P value =0.32). The mean colon transit time in our study was 51.8 ± 16.3 hours. Conclusion: Functional constipation patients should undergo CTT, especially those who use maneuvers for defecation and those who need more time for defecation.[GMJ. 2012;1(2):48-52]